An approach to the tuberous sclerosis complex - Luis Fernando, Domínguez Valdez; Iliana Nelly, Chávez Sánchez; Reyes Verónica, Cuapanteca; Luis Armando, García Pedraza; López Oscar, Bernal; Varela Diego Fernando, De Santiago; Carlos Alberto, Hernández Jiménez; Carlos Ublester, Cadena Corona; Diana Karen, Saldivar López; Rocha Alejandro, Serment (International Journal of Research in Medical Sciences, 2022)
Tuberous sclerosis is an autosomal dominant disorder with complete penetrance that is characterized by the formation of benign tumors in multiple organs, such as hamartomas in the skin, angiomyolipoma in the kidney, retina, heart, lungs and infratentorial brain tumors, conditioning alterations of neurological type, which condition repercussion on the quality of life of patients.